The Elusive Quest for the Holy Grail of an Impact of EU Funds on Regional Growth - Jan Fidrmuc; Martin Hulényi; Olga Zajkowska (Center for Economic Studies and ifo Institute (CESifo), 2019)
We analyze the impact of EU structural and cohesion funds on economic growth of European regions, using 2SLS to tackle the potential problem of endogeneity, and estimating a spatial model to account for inter-regional spillovers. We use the presence of environmentally protected areas (under the European Union's Natura 2000 program) as instruments for the receipts of funds from the EU Cohesion Policy. We find that the European funds have a significant and positive effect on regional economic growth in the EU. The inter-regional spillovers in the effect of Cohesion Policy on regional growth are found to be important: most of the effect takes place outside of the recipient region rather than inside. However, there is considerable heterogeneity in the effect of Cohesion Policy across individual EU member states: the effect is stronger in the new member states, and weak or negative in the countries hit by the recent austerity measures. Finally, our results confirm the positive impact of institutional quality: improvements in economic development across the EU do not necessarily require only redistribution: institutional reform can also help boost growth performance.
Keywords: C21; C36; F36; E62; O11; P48; 330; regional aid; growth; environmental conservation; 2SLS; spatial model